Inequalities in employment rates among older men and women in Canada, Denmark, Sweden and the UK - Ashley McAllister; Lee Bentley; Henrik Brønnum-Hansen; Natasja Koitzsch Jensen; Lotta Nylen; Ingelise Andersen; Qing Liao; Theo Bodin; Cameron Mustard; Bo Burström (BMC, 2019)
Abstract Background In most developed countries, governments are implementing policies encouraging older persons to work past 65 years to reduce the burden on societies related to disability benefits and pension payments. Despite this push to extend working lives, we know little about who already works past this age and any inequalities that may exist. Our study investigates the employment rates of those aged 65-75 years of age by educational level, health status and sex in Canada (CAN), Denmark (DK), Sweden (SE) and the United Kingdom (UK). Secondly, we aim to relate findings on employment rates to prevailing policies in the different countries, to increase the understanding on how to further extend working lives. Methods We used nationally representative cross-sectional survey data from the 2012-2013 Canadian Community Health Survey, 2013/14 Survey of Health, Ageing and Retirement in Europe for Denmark and Sweden and the 2013 English Longitudinal Study of Ageing to examine employment rates for those aged 65-75 years by sex, educational level and health status (having limiting longstanding illness (LLI) or not). Results Employment rates decline by age, but we see a linear decline in CAN and the UK compared to an initial decline then a plateau of employment rates from 66 to 68 years in DK and SE. Employment rates among persons aged 65-75 years were lower in the UK than in CAN, DK and SE. Among women, employment rates were highest in SE. Women with low education and a LLI had considerably lower employment rates than men with low education and a LLI (employment rates for men ranged from 27% to 12% compared with employment rates for women which ranged from 12% to 0%). Conclusions Our results suggest that educational level, sex and health all play a role in extending working lives. The variation in employment rates between the four countries implies that policies do matter, but that social differentials show that policies cannot be 'one size fits all'. Policy-makers must consider different groups (i.e. low-educated women with a LLI) when designing policies to extend working lives.